2016
DOI: 10.1002/chem.201603041
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free Difunctionalization of Activated Alkenes in Water: Efficient Synthesis of β‐Keto Sulfides and Sulfones

Abstract: Difunctionalization of activated alkenes, a powerful strategy in chemical synthesis, has been accomplished for direct synthesis of a series of β-keto sulfides and β-keto sulfones. The transformation, mediated by O2 , proceeds smoothly in water and without any catalyst. Prominent advantages of this method include mild reaction conditions, purification simplicity, and gram-scale synthesis, underlining the practical utility of this methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 71 publications
0
14
0
3
Order By: Relevance
“…In continuation of our research interest in iodine reagent‐mediated reactions, herein we report a metal‐free approach via an iodine‐triggered and expedient dioxygen activation method for the oxysulfonylation reaction towards the synthesis of β‐hydroxysulfones from styrenes (Figure a) . The aerial oxygen was activated for the introduction of an OH group at the benzylic position and the near quantitative synthesis of β‐hydroxysulfones was achieved from styrenes and sulfonyl hydrazides using pyridine as additive (10 mol%) and iodine (10 mol%) as catalyst .…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our research interest in iodine reagent‐mediated reactions, herein we report a metal‐free approach via an iodine‐triggered and expedient dioxygen activation method for the oxysulfonylation reaction towards the synthesis of β‐hydroxysulfones from styrenes (Figure a) . The aerial oxygen was activated for the introduction of an OH group at the benzylic position and the near quantitative synthesis of β‐hydroxysulfones was achieved from styrenes and sulfonyl hydrazides using pyridine as additive (10 mol%) and iodine (10 mol%) as catalyst .…”
Section: Resultsmentioning
confidence: 99%
“…Sulfonyl radicals are transient intermediates that undergo a range of reactions, including with alkenes 7 and alkynes. 8 However, examples of their reactivity with aromatic rings are scarce: 1 the groups of Deng and Kuhakarn have independently reported sulfonylation of indoles at the C-2 position using sodium sulfinate salts under oxidative conditions, 9 Li and coworkers have reported on hypervalent iodine-mediated sulfonylation of anilides with aryl sulfonyl chlorides, 10 and sulfonyl radicals have been implicated in transition-metal-catalyzed directed C–H sulfonylations.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Lei group [67] reported a catalyst‐free strategy for oxosulfonylation of activated alkenes (alkenes having a good leaving group at α ‐position like phosphate ester) 26a with aryl sulfinic acids 26b in water medium for synthesis of a series of β ‐keto sulfones 26c with up to 66% yield ( Scheme 26 ) . The authors also demonstrated that aryl thiols produced β ‐keto sulfides with good to excellent yields.…”
Section: Different Oxosulfonylation Methodsmentioning
confidence: 99%
“…In light of its extensive efficacies, numerous protocols of oxosulfonylation such as metal-catalyzed oxosulfonylation, [46][47][48][49][50][51][52][53][54][55] organophotocatalyzed oxosulfonylation, [32,[56][57][58] metal-based photocatalyzed oxosulfonylation, [59][60][61] catalyst free photo-induced oxosulfonylation [62][63][64] etc have been developed. Very recently, oxygen triggered oxosulfonylation methods [65][66][67][68][69][70][71][72] show great interest among synthetic organic chemists.…”
Section: Introductionmentioning
confidence: 99%